2010
DOI: 10.1038/hr.2010.79
|View full text |Cite
|
Sign up to set email alerts
|

Losartan inhibits LPS-induced inflammatory signaling through a PPARγ-dependent mechanism in human THP-1 macrophages

Abstract: Macrophages have critical roles in the pathogenesis of atherosclerosis by activating the innate immune system and producing inflammatory cytokines. Accumulating evidence indicates that angiotensin type 1 receptor (AT1R) blockers exert antiinflammatory effects in inflammatory diseases including atherosclerosis. In this study, we investigated the effect of losartan, an AT1R blocker, on the proinflammatory gene expression induced by bacterial lipopolysaccharide (LPS) in a well-defined in vitro human THP-1 macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 27 publications
(31 reference statements)
9
47
0
Order By: Relevance
“…The effects of telmisartan compared well with those of the PPARγ agonist troglitazone [34]. All ARBs tested inhibited LPS-induced pro-inflammatory gene expression in THP-1 cells, which is consistent with the recent report of anti-inflammatory effects of losartan through a PPARγ-dependent mechanism [35]. This order of potency parallels the reported PPARγ agonist activity of the ARBs tested [6,12].…”
Section: Discussionsupporting
confidence: 78%
“…The effects of telmisartan compared well with those of the PPARγ agonist troglitazone [34]. All ARBs tested inhibited LPS-induced pro-inflammatory gene expression in THP-1 cells, which is consistent with the recent report of anti-inflammatory effects of losartan through a PPARγ-dependent mechanism [35]. This order of potency parallels the reported PPARγ agonist activity of the ARBs tested [6,12].…”
Section: Discussionsupporting
confidence: 78%
“…We previously found that macrophage levels were enhanced in Pan02 tumors grown in SPARC−/− mice [23]. Losartan, which has been shown to inhibit inflammatory signaling in macrophages [51] promoted an increase in the M2∶M1 macrophage ratio in tumors grown in SPARC-deficient animals. Losartan treatment did however, negate the increase in Treg recruitment observed in tumors grown in the absence of host SPARC.…”
Section: Discussionmentioning
confidence: 92%
“…(iii) Losartan could exert some of its effect through AT 1 R-independent mechanisms. In this regard, it has been previously reported that losartan inhibits LPS-induced pro-inflammatory gene expression in macrophages by activating the PPARγ (peroxisome-proliferator-activated receptor γ ) pathway rather than by the competitive inhibition of AT 1 R binding to AngII [85]. (iv) Losartan and Ang-(1-7) improve muscle strength in animal models of Duchenne muscular dystrophy through the inhibition of the TGF-β1 signalling pathway [37,86].…”
Section: Discussionmentioning
confidence: 95%